Airline Fleet Assignment and Schedule Planning - Aditya Nugroho (Institut Transportasi dan Logistik Trisakti, 2014)
Airline fleet assignment plays important role for efficient operation of airlines. In order to save costs from the procurement and maintenance of extra aircrafts, the airline operators would always seek to minimise the fleet size, while at the same time being able to operate all the flights without shortage of aircraft. Therefore, the daily flight schedule of the airline must be prepared in such a way that the destinations can be served with minimum number of aircrafts. Considering this, there is huge prospect of using optimisation techniques to select the optimum mix of various types of aircrafts in the airline fleet and thereby to produce an optimum flight schedule.